LOW-INVASIVE TECHNOLOGIES OF INITIAL SURGICAL D-BRIDEMENT IN POLYTRAUMA AT THE FIRST STAGE OF PROGRAMMED MULTISTAGED SURGICAL TREATMENT - Yu. A. Shcherbuk; V. A. Kozlov; K. P. Golovko; I. V. Gaivoronskiy; V. I. Badalov; O. D. Madai; A. S. Bagnenko; Yu. F. Golinskiy; D. A. Yakimchuk; D. Yu. Madai (Вестник хирургии имени И.И. Грекова)
The authors described the variants of initial surgical d-bridement on the basis of experience of treatment of 183 patients of multistaged treatment program.